Phylogenetics of bactrocera fruit flies in Malaysia with reference to selected host fruits / Joey Ee Uli - Joey, Ee Uli (2013)
Bactrocera carambolae and Bactrocera papayae fruit flies, also known as the carambola and papaya fruit fly respectively, are significant pest fruit flies in Malaysia. They are capable of causing losses in the agricultural industry by infesting host fruits and making them unable to be sold. These two species are grouped in the Bactrocera dorsalis species complex, and are oftentimes difficult to distinguish from one another due to similar and intermediate morphological characteristics. A precise method for identifying pest fruit flies is important to properly monitor the infestation of host fruits, for the purpose of quarantine management. The aims of this research are to determine the effect of locations and host fruits in the phylogenetics of Bactrocera carambolae and Bactrocera papayae, to determine the phylogenetic relationships between Bactrocera carambolae and Bactrocera papayae, and to determine the ability of the selected molecular markers (COI, COII, and cytb) in distinguishing Bactrocera carambolae and Bactrocera papayae. To determine the taxonomic position between Bactrocera carambolae and Bactrocera papayae, three molecular markers, COI, COII, and cytb, were utilized. Infested host fruits were collected from two locations in Peninsular and East Malaysia (Serdang and Sarawak), and fruit fly specimens were hatched and identified based on morphological characteristics. Molecular phylogenetic analyses using maximum likelihood, Bayesian Inference, Neighbor-Joining, and haplotype network reconstruction based on COI, COII, cytb, and the combination of the three molecular markers, were not able to differentiate Bactrocera carambolae and Bactrocera papayae as two distinct species as they tend to group together within the same clade. Bactrocera carambolae and Bactrocera papayae specimens also tend to group together within the same clade as other members of the Bactrocera dorsalis complex. This suggests that Bactrocera carambolae and Bactrocera papayae could iii possibly belong to the same species. The fruit flies hatched from different host fruits collected from Serdang could not be distinguished using the three mitochondrial DNA markers, however, the fruit flies hatched from host fruits collected from Sarawak tend to group separately from the Serdang specimens. This suggests that the fruit flies collected from Sarawak were genetically different from the fruit flies collected from Serdang.